2012
DOI: 10.1017/s0007123412000051
|View full text |Cite
|
Sign up to set email alerts
|

Global Migration and Political Regime Type: A Democratic Disadvantage

Abstract: An indicator of globalization is the growing number of humans crossing national borders. In contrast to explanations for flows of goods and capital, migration research has concentrated on unilateral movements to rich democracies. This focus ignores the bilateral determinants of migration and stymies empirical and theoretical inquiry. The theoretical insights proposed here show how the regime type of both sending and receiving countries influences human migration. Specifically, democratic regimes accommodate fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 32 publications
3
57
0
2
Order By: Relevance
“…In the study of international relations, strong reciprocity often exists among a large number of dyads. Previous research has found various levels reciprocity in the context of bilateral trade (Ward and Hoff 2007), interstate conflict (Ward, Siverson, and Cao 2007), and global migration (Breunig, Cao, and Luedtke 2012). We lack empirical evidence from previous research on the reciprocal nature of investment stocks.…”
Section: Property Rightsmentioning
confidence: 79%
“…In the study of international relations, strong reciprocity often exists among a large number of dyads. Previous research has found various levels reciprocity in the context of bilateral trade (Ward and Hoff 2007), interstate conflict (Ward, Siverson, and Cao 2007), and global migration (Breunig, Cao, and Luedtke 2012). We lack empirical evidence from previous research on the reciprocal nature of investment stocks.…”
Section: Property Rightsmentioning
confidence: 79%
“…As the electorate throughout all industrialized democracies can be described as highly critical of immigrants and latently xenophobic (see for example Citrin et al, 1997;Sides and Citrin, 2007), and public policy in democracies is accountable to the preferences of the electorate, liberalizing citizenship and immigration policies becomes a challenging task for democratic governments (Breunig, Cao and Luedtke, 2012). However, a law-making process behind closed doors with as little public attention as possible should generally favor liberalizing change (Givens and Luedtke, 2005).…”
Section: Public Opinion and Electoral Competitionmentioning
confidence: 99%
“…A study by Breunig et al (2012) [7] counter the cases of unstable political condition of a country; they claimed that polity of the sending country has a positive effect on migration but negative effect on the receiving country, which means that the number of migrants is affected by the barriers to entry and freedom of exit from sending and receiving country.…”
Section: Political Stabilitymentioning
confidence: 99%